SIAF and friendly consultation, analysis of public policies in the framework of public management modernization (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The purpose of this article is to highlight the use of SIAF and friendly consultation as tools for the analysis of public policies within the framework of public management modernization. Public policies are a set of state actions for the population subscribed in a forum of national agreement carried out in 2002, where 35 agreements were reached, organized in four general lines, with the participation of the three levels of government and the main political and social institutions of the country. These agreements constitute state policy actions and government policies of national scope. In order to be implemented, these actions require a public budget; this is where the SIAF and the friendly consultation for the correct budget management with efficiency and effectiveness of both income and expenditures in all public institutions of the state intervene